Surface treatment of silica nanoparticles for stable and charge-controlled colloidal silica - Kim KM (Dove Medical Press, 2014)
Kyoung-Min Kim,1 Hye Min Kim,1 Won-Jae Lee,2 Chang-Woo Lee,3 Tae-il Kim,4 Jong-Kwon Lee,5 Jayoung Jeong,5 Seung-Min Paek,2 Jae-Min Oh1 1Department of Chemistry and Medical Chemistry, College of Science and Technology, Yonsei University, Gangwon-do, Republic of Korea; 2Department of Chemistry, Kyungpook National University, Taegu, Republic of Korea; 3Battelle-Korea Laboratory, International Center for Converging Technology, Korea University, Seoul, Republic of Korea; 4Department of Biosystems and Biomaterials Science and Engineering, College of Agriculture and Life Sciences, Seoul National University, Seoul, Republic of Korea; 5Toxicological Research Division, National Institute of Food and Drug Safety Evaluation, Chungchungbuk-do, Republic of Korea Abstract: An attempt was made to control the surface charge of colloidal silica nanoparticles with 20 nm and 100 nm diameters. Untreated silica nanoparticles were determined to be highly negatively charged and have stable hydrodynamic sizes in a wide pH range. To change the surface to a positively charged form, various coating agents, such as amine containing molecules, multivalent metal cation, or amino acids, were used to treat the colloidal silica nanoparticles. Molecules with chelating amine sites were determined to have high affinity with the silica surface to make agglomerations or gel-like networks. Amino acid coatings resulted in relatively stable silica colloids with a modified surface charge. Three amino acid moiety coatings (L-serine, L-histidine, and L-arginine) exhibited surface charge modifying efficacy of L-histidine > L-arginine > L-serine and hydrodynamic size preservation efficacy of L-serine > L-arginine > L-histidine. The time dependent change in L-arginine coated colloidal silica was investigated by measuring the pattern of the backscattered light in a Turbiscan™. The results indicated that both the 20 nm and 100 nm L-arginine coated silica samples were fairly stable in terms of colloidal homogeneity, showing only slight coalescence and sedimentation. Keywords: silica, nanoparticles, surface charge, colloidal stability, turbidity, amino acids